FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI USILA DI KOTA PADANG TAHUN 2006 - Elza Enny (Andalas University, Faculty of Public Health, 2006)
The aged is the last segment in human life, where it has been growth and develop from the baby, adult and old. It turn out the increasing number of ages are not followed by good treatment toward of the aged-only about 15,6% of the aged in Padang can be managed by the posyandu (the center for integrated health care at the district). Then, in order to know about nutritional status of the aged therefore we did the research about 'the factors that relating to the nutritional status af the aged in Padang'. The characteristic in this research is analytic to use the cross-sectional study. The research is doing at may 2006 in 2 location is Puskesmas Kuranji sub district Kuranji and Puskesmas Ulak Karang sub district North Padang with 108 samples. The results of this research indicated that 50,9% of the aged are 70 year old, 65,7% are the women, 84,3% live with their family, and 40-60% have physical disturbance problems, meanwhile 50% of the aged have the level of nutritional substances sufficiency with 80% of the suggested number of nutrition sufficiency and 25,9% of the aged have less of nutrition. The statement no significant relationships between ages and life's companion with nutrition intake of the aged, but have inclination of the aged is about 70 years old and stay alone have less of nutrition. Another that, are significant relationship between the sex with nutrition intake, and are significant relationship between nutrition intake (energy/protein) with nutritional status and no significant relationships between fat intake with of the aged nutritional status. Futhermore, there are significant relationships between the ages and life's companion with the nutritional status of the aged, and no significant relationship between the sex and nutritional status of the aged yet there is a tendency that most cases about less of nutrition found in men aged.